Prototype of Automatic Egg Incubator with Internet of Things Based on ESP32 Microcontroller - Mahmuddin; Muhammad Daud; Fakhruddin Ahmad Nasution; Misbahul Jannah; Asran; Azwati Azmin (Journal of Renewable Energy, Electrical, and Computer Engineering, 2026)
Chickens are a type of poultry that reproduce by laying eggs. The increasing demand for chicken meat makes it difficult for farmers to meet consumer demand. Therefore, along with technological developments, a tool for hatching chicken eggs that can work automatically to facilitate hatching is needed. To meet these needs in solving the problem of designing an automatic egg incubator system and the performance of the egg incubator that can be monitored via smartphone, which aims to produce an egg incubator that can be monitored and monitored in real time. The prototype of this tool was built using ESP32 as a processor, one type of sensor as an input device, a fan, a gearbox motor and the blynk application as output devices. The sensor used is a DHT11 sensor that can detect temperature and humidity in the egg incubator box, this tool is also equipped with internet of things as a data output that can be monitored via smartphone. Testing was carried out on free-range chicken eggs with a device capacity of 35 eggs. From the test results, it was obtained that the egg incubator can work well. The number of eggs used for the experiment was 35 eggs. This egg incubator has a 91% success rate, with a 9% failure rate, based on 32 chicken eggs hatching. Therefore, this incubator is suitable for both large and small-scale hatching.